WORK LIFE BALANCE DENGAN STRESS KERJA PADA PERAWAT WANITA MINAHASA UTARA - Minar V Hutauruk; Sunarti Baso; Saly Marla Papeti (Jurnal Riset Multidisiplin Edukasi, 2026)
Work life balance is an important thing in human life, including  workers. Work stress is the consequence of every action and environmental situation that poses excessive psychological and physical demands on a person. The purpose of this study was to find out the relationship between work-life balance and occupational stress in female nurses at Maria Walanda Hospital Maramis North Minahasa Regency.This study was conducted at Maria Walanda Hospital Maramis North Minahasa Regency, The population in this study was female nurses who numbered 44 respondents. The study was conducted in July of the year 2025. This type of study is Analytical Descriptive Method in nature (Cross Sectional). The sampling technique uses Total Sampling. Sample collection used work life balance and job stress questionnaire sheet. Further the data was processed using chi-square test The results of the study showed that there is a relationship of work-life balance with job stress with significance level p = ( α< 0.000).Results of chi-square statistical test with significance level p = ( α< 0.000). This means that there is work-life balance with work stress in female nurses at RSUD Maria Walanda Maramis, North Minahasa RegencyConclusions of this study There is a relationship between work-life balance and occupational stress in female nurses at Maria Walanda Hospital Maramis North Minahasa Regency. Suggestion of the results of this study as basic knowledge for students and for further development in nursing midwifery.